Perovskite Ti3AlC Carbide Splitting in High Nb Containing TiAl Alloys. Issue 1760 (19th December 2014) - Baker, I.; Heilmaier, M.; Kishida, K.; Mills, M.; Miura, S.; Wang, Li; Gabrisch, Heike; Lorenz, Uwe; Schimansky, Frank-Peter; Stark, Andreas; Pyczak, Florian
ABSTRACT Transmission electron microscopy has been used to investigate the morphological development of the perovskite (P-) Ti3AlC carbides in the Î³ matrix of a Ti-45Al-5Nb-0.75C alloy during annealing. P-Ti3AlC carbides in the Î³ matrix initially have a needle-like shape but during annealing at 800 Â°C they change to a plate-like shape. In the needle-like shape the carbides are orientated parallel to the [001] direction of the matrix. They extend along the [100]Î³ or [010]Î³ direction into plates later and subsequently split into sub particles after extended annealing. It is proposed that the elastic interaction energy between the split sub domains may be the reason that this decomposition into sub-particles is energetically favorable.